Peranan Istri Nelayan dalam Meningkatkan Pendapatan Rumah Tangga - Rifdahyanti Rifdahyanti; La Harudu; Andrias Andrias; La Ode Amaluddin (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
The role of fishermen's wives has a great influence in increasing the income of fishermen's households. This study aims to determine the role played by fishermen's wives in the public sector in increasing household income in Boneoge Village, Lakudo District, Central Buton Regency. Determination of sampling was carried out by simple random sampling of 34 fishermen's wives. The results of the study showed that the role of fishermen's wives in addition to working in the domestic sector as housewives also works in the public sector in the economic sector in helping the family economy to increase family income. The contribution or role of fishermen's wives in increasing family income is 51.52% with an average family income of fishermen's wives who have worked or have side jobs of IDR. 2,488,235. Based on this income, the average total family income as a whole is IDR. 4,829,411. So that wives have a fairly large role or contribution in increasing family income. In addition, it can be seen that the contribution of fishermen's wives' income to the family is very influential in increasing family income because the income of fishermen's wives is higher than that of husbands where almost every day there is an income from the productive activities of fishermen's wives.